From The History Of Formation Of Medical Ecological Culture In Young People (Based On Requests From The Population) - Nozima Karimova (International Scientific and Current Research Conferences, 2021)
This thesis discusses some situations from the history of the formation of medical ecological culture in youth during the Soviet era. We analyze the extent to which industrial enterprises have harmed the environment, as well as the objections expressed by the population. We will also consider the fact that the drying up of the Aral Sea has had devastating consequences for the region, and the spread of various diseases among the population. The proposals made by scientists in overcoming such tragedies are also analyzed.